A Web Based System For Human Capital Outsourcing - SRIKRISHNA PRASAD (2009)
INTERNAL GUIDE : Swarnalatha R Rao . EXTERNAL GUIDE : Saravana Rajan G USN No : 1MJ08SCS15 CARRIED OUT AT : Celestial V Solutions Bangalore-560 011 ACC NO : PC81
Keywords: M.Tech Computer Science